Careless in red - George, Elizabeth (Harper, 2008)
After his wife's murder, Scotland Yard's Thomas Lynley retreats to Cornwell and his grief. While hiking along the coast, he discovers the body of a young man who appears to have fallen to his death. It soon becomes apparent, however, that a killer is at work, and Lynley finds himself both a witness and a suspect.